Impacts of anthropogenic climate change on meteorological drought in China - Dai, Ran; Huang, Jinlong; Chen, Ziyan; Zhou, Jian; Havea, Peni Hausia (Frontiers in Earth Science, 2024)
Drought, being one of the most devastating natural disasters, has a far-reaching impact. In the context of global warming, it becomes crucial to quantitatively and scientifically assess the effects of anthropogenic climate change on meteorological drought in China. This assessment not only enhances our understanding of anthropogenic climate change but also aids in formulating more effective strategies for managing the risks associated with meteorological drought. This study employs the standardized precipitation evapotranspiration index (SPEI) to compute drought events by utilizing both observational data and counterfactual climate data (i.e., detrended observations). Subsequently, it analyzes the impact of anthropogenic climate change on the characteristics of drought, including frequency, intensity, duration, and affected area, in China as well as nine major river basins from 1960 to 2019. The outcomes of the analysis reveal that based on observational data, there is a discernible upward trend in the frequency, intensity, duration, and affected area of meteorological droughts in China. Notably, the regions experiencing an increase in frequency, intensity, and duration are primarily situated in the northeastern part of the Northwestern Rivers basin, the central and western parts of the Yellow River basin, the central and northern parts of the Yangtze River basin, the western part of the Southeastern River basins, and the eastern part of the Pearl River basin. Conversely, when considering a counterfactual climate scenario, the frequency and intensity of meteorological droughts in China demonstrate an upward trend, while the duration and affected area exhibit a downward trend. The impact of anthropogenic climate change on China has been evident in the increased frequency, intensity, duration, and affected area of droughts. Anthropogenic climate change is highlighted as the primary factor influencing the observed drought characteristics changes in China, with contribution rates of 84.67%, 75.25%, 190.32%, and 133.99% for changes in the increased drought frequency, intensity, duration, and affected area, respectively. These changes have significant implications for water resource management and agricultural practices in the affected regions.